ASSISTANT TO A JUDGE IN COMMON COURTS - STRUCTURAL POSITION AND RANGE OF ACTIVITIES - Małgorzata, Arkuszewska Aneta; Anna, Kościółek (Anales Universitatis Apulensis Series Jurisprudentia, 2013)
The institution of the assistant to a judge originated relatively recently as it was introduced to the Polish legal system in 2001 by the Common Courts Organization Act. It was not included in previous legal regulations relating to common courts organization, i.e. the Regulation of 6 February 1928 and the Act of 20 June 1985, though the provision of the Article 265 § 2 of the Regulation of 1928 provided that judicial secretaries could independently perform certain judicial activities in cases stipulated by the law, and in the event of dissatisfaction with the secretary’s decision, a judge or a court adjudicated. However, the aforementioned competences of the judicial secretary currently resemble more of a court referendary’s powers than those of an assistant to a judge. Keywords: Polish legal system, assistant to a judge, common courts organization.